INDONESIAN ISLAMIC JUNIOR HIGH SCHOOL STUDENTS’ SPEAKING ENGLISH AND ARABIC ANXIETY: A COMPARISON - Irfani, Bambang (Smart, 2019)
This article reveals the phenomenon of speaking anxiety in two foreign languages, Arabic and English, simultaneously studied by students of Islamic junior high school in Indonesia.  It is aimed at analyzing the differences of level, causes as well as coping strategies of speaking anxiety in Arabic and English faced by the respondents.A survey inquiry was conducted by employing questionnaires to gather the data of respondents?level, causes and coping strategies of speaking anxiety.  The analysis indicates a similarity of speaking anxiety level of the two languages, yet some major differences regarding the prominent causes occur. Keywords: Speaking anxiety; Arabic; English; Indonesian students